Answers

  • Brainly User
2014-05-24T19:44:27+05:30
(cosec theta - cot theta ) sq. = 1- cos theta/ 1+ cos theta: prove that

Solution :
 Take L.H.S =   (cosecФ - cot Ф ) ^2
                 =  (1/ sin Ф - cos Ф / sin Ф )^2
                = (1 - cos Ф)^2 / sin^2 Ф
               =  ( 1 - cos Ф )( 1 - cos Ф ) / sin^2 Ф
               = ( 1 - cos Ф )( 1 - cos Ф ) / 1 - cos ^2 Ф
Note :
   sin^2 Ф + cos ^2 Ф = 1
=>    sin^2 Ф  = 1 - cos ^2 Ф

     = ( 1 - cos Ф )( 1 - cos Ф ) / 1 - cos ^2 Ф
     = ( 1 - cos Ф )( 1 - cos Ф ) /  ( 1 - cos Ф ) (1+cos Ф)
 Note :
       ( a )^2 - (b)^2 =  (a +b )(a-b)
 = (1- cos Ф) / (1+ cos Ф )  = R.H.S

Hope this is helpful!!!
3 2 3
ohhk sry Mr.Perfect :P
@sweety better not to comment :p
ohh fyn better not to talk too -_-
@sweety ok koi naii .. karlo comment :p
@sweety ok koi naii .. karlo comment :p